PENYERAPAN MATERI AJAR MELALUI PENGGUNAAN MEDIA VIRTUAL ONLINE DI SEKOLAH MINGGU - Yusnoveri Chung (STT Saint Paul Bandung, 2021)
The lives of Sunday School children during the Covid-19 pandemic faced two different conditions. The first condition is that the stewardship of the children's Sunday School must continue and be sustainable. The second condition is that the pandemic is a strict restriction; hence physical contact and social interaction are impossible. These are challenges and at once opportunities for the church, especially the Sunday School teachers, in responding to them. Indonesian Anglican Church Ichthus Congregation of Medan responds that establishing a zoom platform for meeting the spiritual needs of Sunday School children is worthy of appreciation. Preliminary findings through a study of the provision of questionnaires to 32 respondents indicate that virtual online allows becoming a teaching and learning instrument in these difficult times of pandemic. However, its use must be accompanied by teachers' creativity and efforts to increase the absorption of teaching materials. Using a quantitative method with the Likert scale questionnaire to measure the response to some questions shows a benchmark for the material's absorption level, which is estimated to be above the minimum quantity. This is undoubtedly a great hope for the church and, in this case, the Sunday School to improve and be qualified in using media technology and mastery of teaching materials with a touch of creativity that can attract Sunday School children to grow in their spirituality.